Pengaruh Persepsi Kualitas Pelayanan, Persepsi Kualitas Produk Dan Trust Terhadap Kepuasan Dan Loyalitas Mahasiswa (Studi Pada STIE Adi Unggul Bhirawa Surakarta) - Anggoro Panji Nugroho - STIE AUB Surakarta; Anton Respati Pamungkas - STMIK AUB Surakarta (LPPM Universitas Bina Sarana Informatika, 2015)
Abstract - The purpose of this study was to determine either partially or simultaneously on the influence the perception of service quality, perceived product quality, trust to customer satisfaction and loyalty student at STIE Adi Unggul Bhirawa (STIE ”AUB”) Surakarta. This study is a survey research. Data was collected by distributing questionnaires to the respondents a number of 100 students. The data has been collected tested. The test used is a model of path analysis, t test, F test, test R2 and linearity test.T-test performed showed the perception of service quality, perceived product quality, trust and customer satisfaction significantly influence student loyalty at mahasiswa pada STIE Adi Unggul Bhirawa (STIE ”AUB”) Surakarta. The simultant test result (F-test) shows the perception of service quality, perceived product quality, trust and customer satisfaction significantly influence loyalty student at STIE Adi Unggul Bhirawa (STIE ”AUB”) Surakarta. Results of analysis known that the path is not capable of satisfaction as an intervening variable between the influence of service quality perception, perception of product quality, trust the loyalty of the students. While the test results R2 of 0.993, or 99.3%, which means that the variability of the dependent variable that can be explained by the variability of independent variables by 99.3% while the rest (0.7%) is explained by other variables not included in the regression model. Keywords: service quality perception, perception of product quality, trust, satisfaction, loyalty